Preparation of Basundi Using Ashwagandha for value addition - Modi, Lalita; Pinto, Suneeta; Prajapati, P. S.; Suvera, Priyanka (Indian Journal of Dairy Science, 2023)
The objectives of the present study was to develop an acceptable quality basundi incorporated with Ashwagandha powder . Four batches of Basundi were prepared using three different levels of Ashwagandha powder viz. 0 (P1), 0.20 (P2), 0.25 (P3) and 0.30 (P4) % (w/w of milk). Addition of ashwagandha powder up to 0.25% i.e. P3 was found to be acceptable. In order to evaluate the effect of level of sucrose on its acceptability, P3 Basundi was incorporated with three level of sugar viz. 5, 6 and 7 % (w/w of milk) and it was found that Basundi prepared using 6 % sugar was most acceptable. Cardamom was found most suitable background flavour on basis of sensory score among three different flavors viz. cardamom, saffron and nutmeg when added at the rate of 0.25 % w/w of Basundi. Based on the results obtained in this study a method for preparing Basundi using Ashwagandha powder was developed. The standardized method involved use of mixed milk (fat: SNF ratio of 0.5), addition of 0.25 % Ashwagandha powder and 6 % sugar (w/w of milk) and using cardamom flavour @ 0.25% w/w of Basundi. The total score of the developed product was 90.13 indicating that the product could be graded as excellent quality based on the 100 point score card suggest by BIS for sensory evaluation of milk.